Monopoly Game as Learning Media for Children aged 5-6 Years in Rumbia, Central Lampung Regency - Tri Okta Handayani; Khasan Ubaidillah (Journal of Childhood Development, 2022)
Monopoly game is one of the most popular board and group games in the world, so it will be very easy to introduce the game of monopoly, because most children already know the game. Monopoly games to develop children's cognitive abilities have never been done as a learning medium in Raudhatul Athfal (RA) Darussalam Reno Basuki, Rumbia District, Central Lampung Regency. The purpose of this study was to develop a monopoly game in Raudhatul Athfal (RA) Darussalam Reno Basuki, Rumbia District, Central Lampung Regency. Types of research and development (research and development). The development procedure according to the ADDIE model consists of five stages, namely Analysis (analysis), design (design), development (development), implementation (implementation), evaluation (evaluation). Based on the results of the study, it can be concluded that the development of monocolic game products that were made then went through a validation stage by several experts before being implemented. This validation is carried out by media experts and material experts who are experts in their fields. The validation results from media experts can be seen that monocolic games get an average score of 4 with a percentage of 100%, so it can be said that monocolic games are very feasible. While the validation results from material experts can be seen that monocolic games get an average score of 3.6 with a percentage of 90%, so it can be said that monocholic games are very feasible. The development of monocolic games is effective in increasing the development of cognitive aspects of early childhood.